[OP.3B.03] INFLUENCE OF SUBCLINICAL RENAL DAMAGE ON EARLY VASCULAR AGING IN PATIENT WITH SYSTEMIC LUPUS ERYTHEMATOSUS. (September 2016) - Morreale, M.; Mule', G.; Cusumano, C.; D'Ignoto, F.; Cacciatore, V.; Geraci, G.; Cottone, S.
Abstract : Objective: It is well known that kidney is frequently involved in patients with Systemic Lupus Erythematosus (SLE) However, conflicting data exist about the impact of renal involvement on vascular damage in this group of patients. The aim of this study was to evaluate the influence of renal damage on assessed by aortic pulse wave velocity (aPWV), evaluated a by intima-media thickness (IMT) measurement and assessed by renal resistive index (RRI) measurement, in patients with SLE. Design and method: We enrolled 52 SLE subjects (mean age 39 ± 12 years), divided in two subgroups according to ACR/SLICC classification: patients with lupus nephritis, (LNG), and individuals presenting other features of SLE (Non Lupus Nephritis group, NLNG), compared to 20 age and sex matched healthy subjects. Each patient performed routine blood chemistry, ultrasonographic renal RI, ambulatory blood pressure measurement (ABPM), aPWV through an oscillometric device and ultrasound evaluation of carotid IMT. Results: These groups did not differ regarding clinical and demographic characteristics and 24-hour blood pressures Despite this, lupus patients showed higher values of IMT (ANOVA p = 0.0001), of aPWV (p < 0.01) and of RRI (p = 0.02) when compared to those of CG. NLNG showed similar values of IMT, aPWV, RRI and a lower percentage of patient treated with immunosuppressive drugs when compared to LNG (p = 0.0001). When the SLE patients were re-classified according to KDIGO classification, in 1) patients without Cronich Kidney Disease: NCKD), 2) patients with preclinical renal damage (PCKD) and 3) patients with clinical renal damage we observed that PCKD group showed higher values of IMT and aPWV in comparison to those of CCKD (both p = 0.001) and of NCKD groups (both p = 0.001), but similar RRI (p = ns). The percentage of patients treated with immunosopressive drugs was similar in PCKD group when compared to that of NCKD group, but lower than CCKD group (p = 0.05). Conclusions: Our results suggest that a good treatment in lupus nephritis leads to a reduced vascular involvement, and overall, being subclinical renal damage a powerful predictor of cardiovascular events, SLICC criteria should be reconsidered in order to avoid an under diagnosis and treatment of renal involvement in SLE patients.